Novel sodium percarbonate-MnO2 effervescent tablets for efficient and moderate membrane cleaning. (15th July 2022) - Li, Boda; Han, Ziwen; Ma, Jun; Qiu, Wei; Li, Wenqian; Zhang, Bin; Zhai, Xuedong; Ding, An; He, Xu
Highlights: Novel SPC-MnO2 effervescent tablets are constructed for membrane cleaning. More than 95% flux recovery is achieved via free radicals and oxygen. SPC-MnO2 system shows more moderate oxidation property compared to H2 O2− MnO2 system. Moderateness of cleaning property is due to the transformation from O H to C O 3 − . Abstract: Membrane flux recovery efficiency and durability are two key factors closely associated with the practical application for membrane cleaning process. However, conventional chemical membrane cleaning method by soaking the whole membrane module in highly concentrated chemical reagents has prominent drawbacks including the low mass transfer efficiency of reagents, long period of washing time, and the potential threat to membrane structure. Herein, for the first time, we report a facile approach to fabricate the sodium percarbonate-MnO2 effervescent tablets which show bubbling reaction to release oxygen and free radicals when being dispersed in water for membrane cleaning. Due to the synergistic effect of MnO2 and sodium percarbonate, the tablets are highly effective to clean the membrane fouled by humic acid within 5 min, with the terminal membrane flux being recovered from 0.50 to 0.95, and the irreversible fouling resistance being reduced by more than 90%, which is prominently more efficient than the conventional chemical cleaning methods. Moreover, even by consecutive membrane fouling and cleaning for 6 times, the membrane flux and filtration efficiency of the membrane could still be kept almost constant, and the moderateness of this membrane cleaning method was also verified by the systematic microscopic analysis. For mechanism study, results of Electron Spin Resonance (ESR) and quenching experiments indicated that the high-efficiency and robust durability of sodium percarbonate-MnO2 (SPC-MnO2 ) system for membrane cleaning was mainly attributed to the abundantly generated hydroxyl radicals and secondary free radicals (i.e. carbonate radicals). Conclusively, compared with the conventional membrane cleaning method with liquid cleaning reagents, the novel SPC-MnO2 system with remarkable advantages in terms of convenience and membrane cleaning performance demonstrated high potential for the wide application in practice. Graphical abstract: Image, graphical abstract